A DVP-Based Bridge Architecture to Randomly Access Pixels of High-Speed Image Sensors. (26th January 2011) - Khan Khan, Tareq Hasan Tareq Hasan; Wahid Wahid, Khan A. Khan A.
Abstract : A design of a novel bridge is proposed to interface digital-video-port (DVP) compatible image sensors with popular microcontrollers. Most commercially available CMOS image sensors send image data at high speed and in a row-by-row fashion. On the other hand, commercial microcontrollers run at relatively slower speed, and many embedded system applications need random access of pixel values. Moreover, commercial microcontrollers may not have sufficient internal memory to store a complete image of high resolution. The proposed bridge addresses these problems and provides an easy-to-use and compact way to interface image sensors with microcontrollers. The proposed design is verified in FPGA and later implemented using CMOS 0.18 um Artisan library cells. The design costs 4, 735 gates and 0.12 mm 2 silicon area. The synthesis results show that the bridge can support a data rate up to 254 megasamples/sec. Its applications may include pattern recognition, robotic vision, tracking system, and medical imaging.